تعليم مهارة الكلام في المدرسة الثانوية في إندونسيا ونيجيريا - Nuril Mufidah; Abdur-Rasheed Mahmoud Mukadam; Imaduddin Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
تهدف هذه الدراسة إلى وصف عن أساليب التدريس في المدارس الثانوية في إندونيسيا ونيجيريا. الطريقة المستخدمة في هذه الدراسة هي البحث النوعي الوصفي الميداني. ومجتمع البحث: المدير، ومدرسي اللغة العربية في المدرسة الثانوية وطلاب المدارس في إندونيسيا النيجيريا. كانت طرق جمع البيانات المستخدمة هي الملاحظة، والمقابلات، والوثائق، مع التحليل الفني لبيانات التثليث. تشير نتائج الدراسة إلى أن تعلم مهارة التحدث للمدرسة الثانوية في إندونيسيا يستخدم طريقة السمعية الشفهية. تبدأ عملية التعلم مع ذكر وقراءة المفردات من قبل المدرس، ثم يشارك الطلاب في النطق ثلاث مرات. يتم تقييم التعلم من خلال تقديم أسئلة للطلاب حول المفردات التي تم منحها ثم يقوم الطلاب بالإجابة اللفظية. كما يُطلب من الطلاب وضع جمل من المفردات التي يعطيها المعلم شفهيًا. إن استخدام هذه الطريقة تشجع الى نجاح البيئة العربية حيث يتكلم الطلاب اللغة العربية يوميا، وتؤدي الى وجود جو تعلم تفاعلي وتواصلي وممتع حتى لا يشعر الطلاب بالملل. وأما تعليم مهارة الكلام في المدرسة الثانوية بنيجيريا يعتمد اعتمادا كليّا على تعويد التلاميذ على الكلام باللغة العربية وتنمية خبراتهم الكلامية بأشكال متنوعة من الحوار والمناظرة أو المسابقة وغيرها. ويحدث ذلك تحت هيمنة المدرس الذي يلاحظ في كلامهم مواضع النقص والإخفاق، فيقوم بالتصحيح مشفوعا بالبيان والتوضيح والتوجيه المقنع. من بعض وجوه الاتفاق والاختلاف بين إندونسيا ونيجيريا؛ حيث كان الاتفاق في كثير من الأنظمة التدريسية والمشاكل التي تواجه التلاميذ في تعليم مهارة الكلام مع اهتداء المدرس إلى كيفية تبديد شمل هذه المشكلات مع سعيه الحثيث لإيجاد الحلول الناجعة. This study aims to describe speaking proficiency teaching methods for high school level in Indonesia and Nigeria. The method used in this study is descriptive qualitative, field research with the subject of the principal, Arabic language teachers, and senior high school in Indonesia and Nigerian school students. Data collection methods used were observation, interviews, and documentation, with technical analysis of triangulation data. The results showed that learning Indonesian conversation skills using the method of sam'iyah syafahiyah (oral audio). The learning process begins with mentioning and reading vocabulary by the teacher, and then students participate in the pronunciation three times. Learning is evaluated by asking questions to students about the vocabulary that has been given, and students respond verbally. Students are also required to make vocabulary sentences given orally by the teacher. The use of this method encourages the success of the Arab environment where students speak Arabic every day and lead to an interactive, communicative and enjoyable learning environment, so students do not feel bored. Teaching speaking skills in secondary schools in Nigeria depends entirely on the ability of students to speak Arabic and develop their verbal skills in various forms of dialogue, debate, competition, etc. This happens under the domination of the teacher, who notes in their words about deficiencies and failures, which are corrected with statements and clarification and convincing guidance. There are similarities and differences between Indonesia and Nigeria, for example the similarities in the teaching system and the problems faced by students in learning speaking skills with the teacher explaining how to solve this problem by finding practical solutions.